Pendampingan Dan Pengembangan Literasi Digital Pada Generasi Santri Milenial Dalam Bingkai Islam Moderat Terintegrasi Dengan Basis Social Entrepreneurship Di Pesantren Kabupaten Jember - Finadatul Wahidah (Lembaga Penelitian, Publikasi Ilmiah dan Pengabdian kepada Masyarakat (LP3M), 2024)
The millennial santri generation has great potential in advancing a moderate Islamic civilization that is inclusive and progressive. However, challenges related to the lack of digital literacy among students are an obstacle to utilizing technology for positive purposes. This service aims to provide assistance and development of digital literacy to the millennial generation of students with an integrated approach with moderate Islamic values ​​and the concept of social entrepreneurship. The methodusedin this service is community development. The communities being developed are the students of Al-Qodiri Islamic Boarding School Jember and the students of Al-Barokah An-Nur Islamic Boarding School Jember. Techniques used in implementing community development methods. Based on the results of the assistance carried out at the Al-Qodiri Jember Islamic Boarding School and the Al-Barokah An-Nur Jember Islamic Boarding School, it can be concluded that the quality of students at the two Islamic boarding schools has improved.on aspects of digital literacy based on social entrepreneurshipit will not be successful if there is no cooperation and active participation from the mentoring subjects, associations and institutions that contribute actively to the Al-Qodiri Jember Islamic Boarding School and the Al-Barokah An-Nur Jember Islamic Boarding School as well as donors who have contributed sincerely. The implementation of mentoring runs effectively and efficiently because it results in developing the quality of HR assetsSantri on aspects of digital literacy knowledge and skills based on social entrepreneurship within the frame of Moderate Islam. In line with the implementation of assistance, the quality of management continues to increaseInstagram and FB Santri DigitalPreneur which contains activities social entrepreneurship within the frame of Moderate Islam.